KARAKTERISTIK DAN KERAPATAN SARANG ORANGUTAN (PONGO PYGMAEUS WURMBII, TIEDEMANN 1808) DI AREAL IUPHHK-HA PT. KARDA TRADERS KABUPATEN LAMANDAU PROVINSI KALIMANTAN TENGAH - Riyadi, Galuh Mochammad; Said, Syafruddin; anto, Eri (Universitas Tanjungpura, 2015)
Orangutans classified in order of primates and including large mammal are arboreal wildlife. Based on CITES the species categorized in Appendix I, while based on IUCN into Endangered category and be fully protected by Indonesian law whose existence is more extinct. Belantikan Hulu forest area as a potential area for animals living, one of which is the orangutan but on the other also involves the use of the area by IUPHHK-HA PT. Karda Traders. The purpose of this research was to know the characteristics and density of orangutan nests, using a transect method with record the discovery orangutan nests along the 1 km. Characteristics nest obtained an average yield orangutan nests diameter is 43.38 to 68.74 cm, diameter trees used as nests about 21.23 to 50.40 cm, height from 8.25 to 17.38 m and a height nest tree used as a nest 10 to 19.75 m. Determinant coefficient values (KP) from regression analysis indicate found nest tree height has a significant relationship to high nest with a range of high nest, Determinant coefficient values (KP) from regression analysis indicate found nest tree height has a significant relationship to high nest with a range from high nest while the results from Mann-Whitney statistic test > 0,005 is not significantly different at the two locations. The position of nest most common positions 1 and 2, the nest class is found that the class C. Aglaia and Syzygium are two genera (genus) are most used as a nest tree C. Density of nest in ex logging area 2012 with a total 2954,14 nests/4km2, while ex logging area 2009 is 2023,38 nest/4km2, the value from nest density is influenced by the availability of feed orangutans and variations in diameter and height of trees in the area. Necessary to keep and sustain tree species nesting orangutans. Key Word: Characteristic, Density, Orangutan nest, PT. Karda Traders